Adolescents’ Perceptions of AI Chatbots as Interpersonal Communication Partners in Bandung - Aurelius Pradipa Sean Aplhafiano; Astri Wulandari; Cut Anindita Pudianti; Jeniver Alleta Tigauw (Universitas Telkom, 2026)
Artificial intelligence (AI) chatbots have increasingly become part of adolescents’ everyday communication practices. This research examines how adolescents in Bandung perceive interpersonal communication with AI chatbots and how these technologies are positioned beyond their functional role as digital tools. Using a qualitative phenomenological approach and purposive sampling, this study involved ten adolescents aged 18–23 years who actively use AI chatbots. Data were collected through in-depth interviews and analyzed using thematic analysis through coding and categorization processes. The findings reveal that adolescents perceive AI chatbots not only as information providers, but also as personal assistants, discussion partners, and emotionally comfortable communication spaces. The speed, flexibility, and non-judgmental nature of AI chatbots responses encourage users to engage in repeated interactions for academic, personal, and daily-life purposes. However, participants also expressed concerns regarding privacy, dependency, and the artificial nature of chatbot empathy. The novelty of this research lies in its exploration of AI chatbots as perceived interpersonal communication partners among adolescents. The study contributes to contemporary communication studies by showing how AI-mediated interaction reshapes communication patterns, openness, and perceptions of social comfort in digital society.